Deep structured populations of geographically isolated nipa (Nypa fruticans Wurmb.) in the Indo-West Pacific revealed using microsatellite markers - Mantiquilla, Junaldo A.; Shiao, Meng-Shin; Lu, Hsueh-Yu; Sridith, Kitichate; Sidique, Siti Nordahliawate M.; Liyanage, Wasantha Kumara; Chu, Ya-Ling; Shih, Huie-Chuan; Chiang, Yu-Chung (Frontiers in Plant Science, 2022)
Nipa (Nypa fruticans Wurmb.) is an important mangrove palm species, but it is understudied due to lack of information on genetic patterns within its distribution range. In this study, we identified 18 informative microsatellite markers to assess genetic variations among local populations in the Indo-West Pacific (IWP). Results showed population stratification based on high genetic differentiation (FST = 0.22131) with Mantel test indicated significance to isolation-by-distance. We found a pronounced differentiation between the west populations in Sri Lanka and east populations in Southeast Asia. The east populations around South China Sea were more genetically similar than those along Malacca Strait and Java Sea. These genetic clines were shaped by ocean circulations and seasonal monsoon reversals as plausible factors. Malacca Strait was confirmed as both genetic and geographic barrier rather than a corridor according to Monmonier plot. Simulations of directional migration indicated a statistically strong contemporary genetic connectivity from west to east where Sri Lankan immigrants were detected as far as Central Philippines via long-distance dispersal. This is the first report on the recent migration patterns of nipa using microsatellites. Assignment of first-generation (F0) immigrants suggested Mainland Southeast Asia as a melting pot due to admixture associated with excess of homozygosity. The western populations were recent expansions that emerged in rapid succession based on phylogram as supported by footprints of genetic drift based on bottleneck tests.